COVID-19 reduced age differences in social motivation - Jiang, Li; Carstensen, Laura L. (Frontiers in Psychology, 2023)
Socioemotional selectivity theory (SST) maintains that when futures loom large, as they typically do in youth, people are motivated to explore. When future time is perceived as more limited, as is typical in old age, people are motivated to pursue emotionally meaningful goals. Because the COVID-19 pandemic primed mortality across the age spectrum, it provided an opportunity to examine whether age differences in social motivation typically observed were also present during the pandemic. We measured social motivation, as operationalized by social preferences, in two studies during peak of the pandemic in 2020. Once vaccines were introduced in 2021, we conducted two additional studies using the same experimental paradigm. As hypothesized, at the peak of the pandemic, social preferences favored emotionally meaningful partners regardless of age. Social preferences differed by age (as reliably observed in research conducted before the pandemic) when vaccines were available. Findings suggest that widely documented age differences in social motivation reflect time horizons more than chronological age.